Nanoparticle trends and hotspots in lung cancer diagnosis from 2006-2023: a bibliometric analysis - Yilun, Wang; Yaojing, Zhang; Hongcan, Shi (Frontiers in Oncology, 2024)
BackgroundLung cancer possesses the highest incidence and mortality rates among malignancies globally. Despite substantial advancements in oncology, it is frequently diagnosed at an advanced stage, resulting in a poor prognosis. Over recent decades, the swift progress of nanotechnology has precipitated the extensive utilization of nanomaterials as carriers in cancer diagnosis and therapy. The deployment of nanoparticles as an innovative diagnostic strategy aspires to enable the earlier detection of lung cancer, thereby permitting earlier intervention and enhancing prognosis. This study endeavors to deepen our understanding of this domain through a comprehensive analysis employing bibliometric tools.MethodRelated articles were retrieved from the Web of Science Core Collection from January 1st, 2006, to December 14st, 2023. Thereaf CiteSpace, VOSviewer and the online platform of bibliometrics (http://bibliometric.com/) were utilized to visually analyze Author/Country/Institutions/Cited Journals/Keyword, et al.ResultsA total of 966 articles were retrieved for this study. The analysis unveils a progressive increase in annual publications within this field, with China at the forefront in publication volume, followed by the United States and India. Moreover, Chinese research institutions, notably the Chinese Academy of Sciences and Shanghai Jiao Tong University, prevail in publication output. Upon exclusion of irrelevant search terms, keywords clustering analysis highlights that “biomarkers”, “sensors”, “gold nanoparticles”, and “silver nanoparticles” are predominant research focuses.ConclusionThis bibliometric study furnishes a quantitative perspective on the extant literature, serving scholars in related fields. Furthermore, it anticipates future research trend concerning nanoparticles and lung cancer diagnosis, thereby aiding in the formulation of project planning and the design of experiments.